Investigating the bi-directional strategy transfer between L2 reading and L2 listening skills - Maghsoudi, Mojtaba; Talebi, Seyed Hassan (System (Linköping), 2025)
This study explored the reciprocal transfer of learning strategies between L2 reading and listening, aiming to determine if teaching strategies in one skill enhances the other and which direction, reading to listening or listening to reading, has a stronger impact. To achieve this aim, a true experimental pretest-posttest design with 163 Iranian EFL students was utilized. The participants were split into three distinct groups: Experimental Group 1, received reading strategy instruction, Experimental Group 2, received listening strategy instruction, and the Control Group received traditional language instruction without a specific focus on strategy, focusing on grammar and translation. Both experimental groups underwent five 90-min sessions of strategy instruction over five weeks. The results demonstrated substantial improvements in both reading and listening comprehension among the experimental groups compared to the control group. Notably, strategy transfer from listening to reading was stronger than from reading to listening, as evidenced by participants in Experimental Group 2 demonstrating greater gains in reading comprehension compared to those in Experimental Group 1 in listening comprehension. The study implies that integrating both reading and listening strategy instruction in language education can foster skill development across modalities, making learning more efficient and promoting interconnectedness between reading and listening skills.